PEMANFAATAN RANSUM BERBASIS BAHAN BAKU LOKAL SEBAGAI PENGGANTI RANSUM KOMERSIL TERHADAP PERFORMA PRODUKSI AYAM PEDAGING - bunga putri febrina; fadhli fajri; fajri Maulana (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
This study aims to determine the effect of using rations based on local raw materials as a substitute for commercial rations on the production performance (ration consumption, body weight gain and ration conversion) of broilers. This study used 100 DOC without male and female separation. The cages used were box cages measuring 75x60x50 cm per unit of 20 units and each unit consisting of 5 chickens. This research method is an experimental method using a completely randomized design (CRD), with 5 ration treatments and 4 replications. The treatment rations were A (100% Commercial / Control Ration), B (75% Commercial Ration + 25% Local Ration) C (50% Commercial Ration + 50% Local Ration), D (25 % Commercial Ration + 75% Local Ration) and E (100% Local Basal Ration). Parameters measured were ration consumption (g/head/week), body weight gain (g/head/week) and broiler ration conversion. The results of the analysis of diversity showed that the provision of rations based on local raw materials as a substitute for commercial rations had a very significant effect (P<0.01) on ration consumption, body weight gain and broiler ration conversion. The results of the DMRT test showed that the provision of rations based on local raw materials as a substitute for commercial rations on ration consumption, body weight gain and ration conversion in treatments B, C and D were not significantly different from treatment A, but significantly higher than treatment E. Based on this study it can be concluded that giving 25% commercial ration + 75% local ration has the same effect as giving 100% commercial ration (control ration). Keywords: Broilers, local rations, production performance